The Fallacies of Mergers Being Acquisitions: Fact or Fiction? - Maneckji, Hilla Shahpur (2006)
The goal of this dissertation study was to examine the fallacies of mergers being acquisitions, which is a very new topic, and that hasn’t been investigated in detail before. The aim of this research was to investigate if major global mergers were acquisitions in camouflage and were only created to portray a false perception. The study was conducted to understand the differences and characteristics between mergers and acquisitions that were further examined taking into account live case studies. That shed further light on strengthening and providing explanations relating to the theory of mergers and acquisitions. With limited sample size and resources, it was very difficult to gather data; hence the results may not be very accurate. Results show that there is no fallacy of mergers being acquisitions and that mergers are not acquisitions in disguise at all, rather they are what they claim to be.